The 144Ce source for SOX. Issue 1 (January 2016) - Durero, M; Vivier, M; Agostini, M; Altenmüller, K; Appel, S; Bellini, G; Benziger, J; Berton, N; Bick, D; Bonfini, G; Bravo, D; Caccianiga, B; et al.
Abstract: The SOX (Short distance neutrino Oscillations with BoreXino) project aims at testing the light sterile neutrino hypothesis. To do so, two artificials sources of antineutrinos and neutrinos respectively will be consecutively deployed at the Laboratori Nazionali del Gran Sasso (LNGS) in close vicinity to Borexino, a large liquid scintillator detector. This document reports on the source production and transportation. The source should exhibit a long lifetime and a high decay energy, a requirement fullfilled by the 144 Ce- 144 Pr pair at secular equilibrium. It will be produced at FSUE "Mayak" PA using spent nuclear fuel. It will then be shielded and packed according to international regulation and shipped to LNGS across Europe. Knowledge of the Cerium antineutrino generator (CeANG) parameters is crucial for SOX as it can strongly impact the experiment sensitivity. Several apparatuses are being used or designed to characterize CeANG activity, radioactive emission and content. An overview of the measurements performed so far is presented here.